Sosialisasi dan Pelatihan Pemadaman Api dengan Metode Karung Basah dalam Penanggulangan Kebakaran Ringan di Dusun Abadi Jaya Desa Ladang Peris - Sukatin Sukatin; Maisarah Gusvita; Anisa Indah Mulyani; Shinta Daratista; Hilma Ruspandi (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Fire extinguishing training using the wet sack method in PKM (Community Service) activities was given to residents of Abadi Jaya Hamlet, Ladang Peris Village. The aim of this service activity is to provide education regarding the importance of knowledge about how to extinguish a fire early if a fire occurs before the fire grows and causes many losses. Before implementing the correct fire extinguishing practice, residents are given material exposure first, and if a light category fire occurs in the environment, use a simple method using wet sacks. Residents are advised to always provide fire extinguishing equipment such as sacks at home as a precautionary measure if a light fire. After providing education through theory, residents were invited to practice how to properly extinguish a fire using wet sacks. This training aims to ensure that residents have direct experience in how to put out a fire so that if a fire occurs, residents do not panic and understand what to do.